PEMBUKTIAN TINDAK PIDANA PORNOGRAFI MELALUI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Nursapira, Nursapira; Oner, Basri; Halwan, Muhammad (Faculty Of Law Bosowa University, 2024)
Penelitian ini bertujuan untuk mengetahui pembuktian tindak pidana pornografi berdasarkan Undang-Undang No. 19 Tahun 2016 dan untuk mengetahui kekuatan alat bukti elektronik sebagai dasar pertimbangan dalam memutus perkara pidana pornografi. Lokasi penelitian di Pengadilan Negeri Makassar dan di Polrestabes Makassar. Tipe penelitian yuridis normatif, menggunakan bahan hukum primer, yang diperoleh secara langsung dari sumber pertama dengan wawancara Hakim Pengadilan Negeri Makassar dan anggota Reskrim Polrestabes Makassar. Data sekunder diperoleh dari survei kepustakaan seperti buku-buku akademis, perundang-undangan, artikel, dan jurnal. Hasil penelitian ini menjelaskan bahwa, pembuktian tindak pidana diatur dalam Pasal 184 ayat (1) KUHAP, alat bukti yang digunakan hakim dalam mengadili terdakwa kasus tindak pidana pornografi. Adapun alat bukti yang digunakan dalam perkara tindak pidana pornografi sebagaimana diatur dakam Undang-Undang No. 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik, berupa informasi dan atau dokumen elektronik tertuang dalam Pasal 1 angka 1, Pasal 1 angka 4, dan Pasal 5 ayat (1) dan ayat (2). dan Pasal 4 ayat (1) Undang-Undang No. 44 Tahun 2008 Tentang Pornografi. Sat Reskrim Polrestabes Makassar menjelaskan kekuatan alat bukti dalam kasus pornografi melalui Undang-Undang Informasi dan Transaksi Elektronik, yakni penyidik mengambil print out hasil dari capture/screenshot dari akun sosial media yang digunakan diberandanya untuk memposting terkait dengan gambar, video, foto, dan lain sebagainya yang memiliki unsur pornografi. This research aims. First: to find out the evidence in the crime of pornography based on Law No. 19 of 2016 concerning Information and Electronic Transactions. Second: to find out the strength of electronic evidence as a basis for judges' consideration in deciding cases of criminal acts of pornography. This research uses normative juridical research type. The research location is at the Makassar District Court Class 1A Special and at the Makassar Police Station. This research uses primary legal material, which is obtained directly from the first source using interview techniques with the Makassar District Court Judge Class 1A Special and the Makassar Police Criminal Investigation Unit. While secondary data, data obtained from literature surveys such as academic books, legislation, articles, and journals that have to do with the content of the author of this research.The results of this study explain that, the proof of criminal acts is regulated in Article 184 paragraph (1) of the Criminal Procedure Code, which is a valid evidence used by the judge in determining the evidence of the defendant's guilt in the case of criminal acts of pornography through the Electronic Information and Transaction Law. And as for the evidence used in solving cases of crimina acts of pornography as regulated in Law No. 19 of 2016 concerning Electronic Information and Transactions, in the form of information and / or electronic documents contained in Article 1 number 1. Article 1 number 4, and Article 5 paragraph (1) and paragraph (2). And Article 4 paragraph (1) of Law No. 44 of 2008 concerning Pornography. The Makassar Police Criminal Investigation Unit explains the strength of evidence in pornography cases through the Electronic Information and Transaction Law where investigators take printouts of the results of captures/screenshots from social media accounts that are used to post related to images, videos. photos, and so on that have pornographic elements.